1990
DOI: 10.1159/000461171
|View full text |Cite
|
Sign up to set email alerts
|

Possibility to Improve Preservation of Whole Blood by Leukocyte-Depletion before Storage

Abstract: In order to evaluate the influence of leukocytes in whole blood on the standard blood bank conditions for storage, we compared several parameters of red cells, leukocytes and platelets in leukocyte-rich and leukocyte-poor whole blood over a storage period of 5 weeks. The leukocyte-depleted units were prepared by filtration with a leukocyte trapping filter (Sepacell R500A). Our data indicate improved storage conditions, made evident by significantly lower cell damage; smaller increases of elastase, β-thromboglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
6
0
1
Order By: Relevance
“…However, PF-4 was increased in plasma after filtration of whole blood, possibly indicating that some platelets un derwent a release reaction during filtration. Riedner et al [19] observed a significant increase in ß-thromboglobulin (ß-TG) after filtration, and interpreted this as the result of filtration-induced mechanical damage of platelets. This phenomenon requires further studies, especially since some leukocyte depletion filters adsorb PF-4, ß-TG and other pro teins, such as C3a and C4a [20].…”
Section: Resultsmentioning
confidence: 99%
“…However, PF-4 was increased in plasma after filtration of whole blood, possibly indicating that some platelets un derwent a release reaction during filtration. Riedner et al [19] observed a significant increase in ß-thromboglobulin (ß-TG) after filtration, and interpreted this as the result of filtration-induced mechanical damage of platelets. This phenomenon requires further studies, especially since some leukocyte depletion filters adsorb PF-4, ß-TG and other pro teins, such as C3a and C4a [20].…”
Section: Resultsmentioning
confidence: 99%
“…This could possibly reflect the release of fibrinogen from platelets during filtration. Other studies have shown release of other platelet α‐granule proteins, such as β‐thromboglobulin, owing to whole blood filtration (Reidner et al , 1990). The release of FV from platelet α‐granules may also explain the increase in plasma FV activity observed with the Terumo filter.…”
Section: Discussionmentioning
confidence: 99%
“…These leukocyte-quires that blood bags and filter be centrifuged, which may lead to reduced centrifuge capacity and require accurate cup packing. Whole blood filtration may well improve the RBCC storage parameters [18] whilst maintaining plasma coagulation factors [18,19].…”
Section: Methodsmentioning
confidence: 99%